2018
DOI: 10.1177/1354068818806630
|View full text |Cite
|
Sign up to set email alerts
|

Party organization and gender in European elections

Abstract: Political parties often monopolize the flow of politicians into elected office making it important to understand when, and under what conditions, parties are more or less likely to promote gender equality in representation. This article argues that party choices to nominate women in elections are conditional on the centralization of candidate selection within the party. Gender quotas and characteristics of the electoral environment have differential effects on candidate lists across party types. Leveraging dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 55 publications
0
19
0
Order By: Relevance
“…For nominations, this literature limited but growing. It mainly looks at selection criteria, such as the pool of available female candidates (see Fortin-Rittberger & Rittberger, 2015), the impact of primaries (Hinojosa, 2012), the size of the group within the party making relevant decisions (Shomer, 2019), the degree to which a party centralised its candidate selection (Aldrich, 2020), the bureaucratisation of the selection process (see Bjarnegård & Zetterberg, 2016) and the incumbency advantage (see Meserve et al, 2020). 1 For the relationship between party characteristics and women's representation there is a larger literature (see O'Brien, 2018).…”
Section: Political Parties and Women's Representationmentioning
confidence: 99%
See 1 more Smart Citation
“…For nominations, this literature limited but growing. It mainly looks at selection criteria, such as the pool of available female candidates (see Fortin-Rittberger & Rittberger, 2015), the impact of primaries (Hinojosa, 2012), the size of the group within the party making relevant decisions (Shomer, 2019), the degree to which a party centralised its candidate selection (Aldrich, 2020), the bureaucratisation of the selection process (see Bjarnegård & Zetterberg, 2016) and the incumbency advantage (see Meserve et al, 2020). 1 For the relationship between party characteristics and women's representation there is a larger literature (see O'Brien, 2018).…”
Section: Political Parties and Women's Representationmentioning
confidence: 99%
“…Parties are central for women's ability to rise in politics because they decide whom they recruit, promote and how much support they give to candidates (see Caul, 1999;Kittilson, 2006Kittilson, , 2011Kenny & Verge, 2016;Pemstein, Meserve, & Bernhard, 2015). According to Aldrich (2020), they matter since 'internal party organisation and strategy shape the party-candidate relationship with respect to gender ' (p. 684-685). Parties offer different opportunity structures for women (Sanbonmatsu, 2002) and even in one of the most gender-equal societies, Sweden, some parties still discriminate against women's abilities to be promoted within these organisations (Folke & Rickne, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, parties in closed-list systems already tend to nominate more women and have been shown to be more reactive to electoral demands when considering the optimum list configuration. 34 In sum, the representation of women depends upon a multitude of elements that must be considered by parties and voters.…”
Section: Legislative Representation In the European Parliament And The National Parliamentsmentioning
confidence: 99%
“…On the other hand, quota legislation has been found to increase the number of female representatives regardless of the type of party list [ 10 , 14 ]. Quotas were found to be most effective in large districts with a closed-list form of proportional representation [ 15 , 16 ]. Jones and Navia, for example, found that quotas did not have an effect on the percentage of women elected in open-list proportional systems, but they did have a positive effect in closed-list proportional systems [ 15 ].…”
Section: Introductionmentioning
confidence: 99%